The North Karelia lessons for prevention of cardiovascular disease - Laatikainen, Tiina; Vartiainen, Erkki; Puska, Pekka (Italian Journal of Public Health, 2007)
Background: As a result of the high cardiovascular disease (CVD) rates in Finland in late 1960’s, which became a source of national concern, a major community based programme for CVD prevention called the North Karelia project was established. Aim: The aim of the project was to carry out a programme of comprehensive community based interventions to reduce coronary heart disease (CHD) mortality and morbidity. Methods: Using lifestyle modification methods and strategies for environmental change the programme aimed to reduce three main risk factors: smoking, elevated blood cholesterol and blood pressure. Several intervention settings and strategies in the community were used. Results: Since the 1970’s the CHD mortality in North Karelia has declined by more than 80%. Major reductions have been seen across the main three cardiovascular risk factors. Among both men and women, total serum cholesterol levels within the population declined by almost 20% and systolic blood pressure by about 10%. Smoking among men decreased from 52% to 33%, while among women a slight increase in smoking prevalence was recorded. Conclusions: The North Karelia project has shown that a comprehensive, determined, theory-based community program can have a meaningful and positive effect on risk factors and lifestyles. Furthermore, these changes are associated with favorable changes in chronic disease rates and the health of the population.